A Continuous 3D-Graphene Network to Overcome Threshold Issues and Contact Resistance in Thermally Conductive Graphene Nanocomposites. (24th January 2017) - Conrado, Federico; Pavese, Matteo
Abstract : In order to overcome thermal resistance issues in polymeric matrix composites, self-standing graphene aerogels were synthetized and infiltrated with an epoxy resin, in order to create conductive preferential pathways through which heat can be easily transported. These continuous highly thermally conductive 3D-structures show, due to the high interconnection degree of graphene flakes, enhanced transport properties. Two kinds of aerogels were investigated, obtained by hydrothermal synthesis (HS) and ice-templated direct freeze synthesis (DFS). Following HS method an isotropic structure is obtained, and following DFS method instead an anisotropic arrangement of graphene flakes results. The density of the structure can be tuned leading to a different amount of graphene inside the final composite. The residual oxygen, known to be detrimental to thermal properties, was removed by thermal treatment before the infiltration process. With 1, 25 wt.% of graphene, using HS method, the thermal conductivity of the polymeric resin was increased by 80%, suggesting that this technique is a valid route to improve the thermal performance of graphene-based composites. When preferential orientation of the filler was present (DFS case), thermal conductivity was increased more than 25% with a graphene content of only 0, 27 wt.%, demonstrating that oriented structures can further improve the thermal transport efficiency.